1992
DOI: 10.1080/00016489.1992.11665428
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Tract Viruses in Otosclerotic Lesions

Abstract: A series of viral antigens, including adenovirus, influenza A and B, parainfluenza types 1 and 3, measles, mumps, respiratory syncytial (RSV) and Epstein Barr (EBV) viruses was studied in a prospective series of stapes specimens from 24 consecutive patients operated on for otosclerosis. The stapes specimens were processed for light microscopy and immunohistochemistry. With the exception of one case of positive specific reactivity for anti-RSV antibody in one multinuclear osteoclastic cell, no specific reactivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Such structures have also been identified in osteoclasts in tissues obtained from patients with PD [146]. When samples from both diseases were examined by immunohistochemistry, conflicting data were obtained which suggested that MV, mumps virus or respiratory syncytial viruses were present [144,147] and these observations were not confirmed in other studies [148]. Molecular approaches have been used to detect viral RNA in PD and OS samples [149,150].…”
Section: Otosclerosis and Paget's Disease Of Bonementioning
confidence: 99%
“…Such structures have also been identified in osteoclasts in tissues obtained from patients with PD [146]. When samples from both diseases were examined by immunohistochemistry, conflicting data were obtained which suggested that MV, mumps virus or respiratory syncytial viruses were present [144,147] and these observations were not confirmed in other studies [148]. Molecular approaches have been used to detect viral RNA in PD and OS samples [149,150].…”
Section: Otosclerosis and Paget's Disease Of Bonementioning
confidence: 99%
“…In 1992, Roald et al (26) published an observation in contradiction with the studies of McKenna et al (16) and Arnold et al (23). They investigated a series of viral antigens, including adenovirus, infiuenza A and B, parainfiuenza types 1 and 3, measles, mumps, respiratory syncytial and Epstein-Barr viruses, in a prospective series of stapes specimens collected from 24 consecutive patients operated on for otosclerosis.…”
mentioning
confidence: 66%
“…However, these studies show that measles virus cannot be found in all otosclerosis cases with the exception of one report describing positive results in all histologically positive cases 20. Others, however, could not find any evidence for the presence of measles 21, 22. In addition, several studies report a decreased expression of anti‐measles IgG in otosclerosis patients compared to controls 23, 24…”
Section: Environmental Factorsmentioning
confidence: 82%